Concentration of Endogenous Secretory Receptor for Advanced Glycation End Products and Matrix Gla Protein in Controlled and Uncontrolled Type 2 Diabetes Mellitus Patients - Dwi Yuniati Daulay; Suryani As'ad; Ali Aspar Mappahya; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2013)
BACKGROUND: Advanced glycation end products (AGE) and their receptor (RAGE) system play an important role in the development of diabetic vascular complications. Recently, an endogenous secretory RAGE (esRAGE) has been identified as a novel splice variant, which lacks the transmembrane domain and is secreted in human sera. Interestingly, it was reported that esRAGE binds AGE ligands and neutralizes AGE actions. Many studies have reported that diabetes mellitus correlates with vascular calcification event and increases progressively in uncontrolled diabetes. Matrix Gla Protein (MGP) is known to act as an inhibitor in vascular calcification. The aim of this study was to observe progress of vascular calcification in uncontrolled diabetes patient by biochemical markers MGP as inhibitor in vascular calcification, via mechanism of AGEs.METHODS: This study was an observational study with cross sectional design on adult type 2 diabetic male patients who were defined by the 2011 Indonesian diabetes mellitus consensus criteria.RESULTS: The results of this study showed that there was a positive significant correlation between esRAGE and HbA1C (r=0.651, p=0.009), and negative correlation between MGP and HbA1C (r=-0.465, p=0.081) in controlled diabetes group. In uncontrolled diabetes group there was a positive significant correlation between MGP and HbA1C (r=0.350, p=0.023), despite the fact esRAGE showed no significant correlation with HbA1C. There was no significant difference in level of esRAGE and MGP in controlled and uncontrolled diabetes group, but MGP showed lower level in uncontrolled diabetes group, contrary to esRAGE that had higher concentration.CONCLUSION: In diabetes condition, complications of vascular calcification are caused by the mechanism of increased AGE formation represented by esRAGE. In diabetes control it is very important to keep the blood vessels from complications caused by vascular calcification.KEYWORDS: type 2 diabetes mellitus, vascular calcification, esRAGE, MGP, HbA1C